Thematic Portfolio in the Course of Teaching Ukrainian Language Teaching Methodology - Nataliya Hrona (Pedagogical Discourse, 2011)
The author of the article arrests attemtion on the problem of quality of the professional training of teachers, shares the experience of using modern technologies in the process of teaching Ukrainian language teaching methodology. The author describes in details the technology of creation of thematic portfolio by the future teachers of primary school, particularly in spelling teaching methodology, because profound knowledge of the spelling material is a requirement of future specialist of primary school.